Analysis of Image Using Singular Value Decomposition Method (International Journal of Innovative Research in Computer Science & Technology, 2020)
Image compression is the process of  reducing the size of an image file while retaining its  quality. When we compress a digital photograph or  graphic file, it maintains the same image resolution but  shrinks the amount of processing data that a computer  uses to view or display that image which ultimately  reduces the memory used for the storage of image files.  There are various algorithms used for image compression.  Linear Algebra(SVD) plays an important role in image  compression. In this paper, we will discuss what is  Singular Value Decomposition (SVD), how to compute singular value decomposition( SVD) andthe size of stored  images is reduced by removing small singular values.We  will use MATLAB to get the final output.
Keywords: Image Compression; Singular Value Decomposition; MATLAB